YOUTH ALTRUISM AND SOCIAL CHANGE - Kosma, Maya (Open Schools Journal for Open Science, 2025)
Youth play a critical role in shaping the future of society. Their energy, creativity, and courage allow them to challenge the status quo and introduce altruistic initiatives that promote justice, equality, and positive change. This presentation examines the importance of altruism among youth, historical and modern examples of youth-driven movements, and the profound benefits of altruism on both personal and societal levels.